(untitled) (Research, Society and Development, 2021)
Objective: To understand the perception of nurses working in the operating room regarding the care offered to patients during the transoperative period in a hospital in the west of Santa Catarina. Methodology: This is a qualitative research, demarcated with assumptions of the ethnographic study, based on interviews and participant observation, which involved a group of nurses working in the operating room of a hospital located in the western region of Santa Catarina. Nurses working in the sector for a period longer than six months were included, with no exclusion criteria. The research was approved by the research ethics committee based on the embodied opinion nº 3.130.468. Results: Three categories emerged from the analysis process: “Care during the surgical experience: nurses in action”, “Perioperative care: possible devices in everyday life” and “Nurses’ perception regarding care in the operating room”. Conclusion: The work overload to which the entire nursing team is exposed is highlighted, which is the main factor that restricts the nurse’s work with the patient in the provision of care, a situation that highlights the need for the nurse or nurse coordinator and another care, both with direct action in providing care to the patient with the team, aiming for an interprofessional work.